An update of a systematic review and meta-analyses exploring flavours in intervention studies of e-cigarettes for smoking cessation - Lindson, N; Livingstone-Banks, J; Butler, A; Levy, D; Barnett, P; Theodoulou, A; Notley, C; Rigotti, N; Chen, Y; Hartmann-Boyce, J (Wiley, 2024)
Aims To determine patterns of e-cigarette flavour use (sweet, tobacco, menthol/mint) in interventional studies of e-cigarettes for stopping smoking, and to estimate associations between flavours and smoking/vaping outcomes. Methods Update of secondary data analyses, including meta-analyses subgrouped by flavour provision and narrative syntheses, incorporating data from January 2004 to February 2024. Eligible studies were identified from a Cochrane review. Studies provided adults who smoked cigarettes with nicotinecontaining e-cigarettes for smoking cessation and provided data on e-cigarette e-liquid flavour use. Outcomes included participants’ flavour use measured at any time, plus smoking abstinence, abstinence from all tobacco or commercial nicotine products, and allocated product use at 6 months or longer, reported as risk ratios with 95% confidence intervals. We assessed risk of bias using the Cochrane Risk of Bias 1 tool. Results We included 25 studies (n=16,748); 21 contributed to subgroup meta-analyses and 18 provided flavour choices. We judged 15 studies at high, seven at low, and three at unclear risk of bias. In studies where participants had a choice of flavours, some switching between flavours occurred (five studies). A preference for sweet (including fruit) flavours over tobacco and menthol was indicated (in 6 of 11 studies); however, there were differences across studies. Subgroup meta-analyses showed no clear associations between e-liquid flavours provided and smoking cessation or study product use. One included study randomised participants to two different flavour conditions and found similar cessation rates and long-term e-cigarette use between arms at 12 months. Conclusions Some people using e-cigarettes to quit smoking switch between e-cigarette flavours during a quit attempt. Sweet flavours may be preferred overall, but this may differ depending on context. Based on intervention studies there is no clear association between the use of e-cigarette flavours and smoking cessation or longer-term e-cigarette use, possibly due to a paucity of data.